(Physico chemical constants of some Indonesian essential oils and their GLC Finger Prints on OV Silicone 101 as Liquid Phase) - Dede Nurlydia; Gasik Dharma; Achmad Moestafa (Balai Besar Industri Agro, 1993)
Essential oils are volatile derived from plants, therefore Glc method of analysis is most recommended.Each oil have differentcomponents and quantitatively can be used as a standard if the same procedure is followed.In case from the different sample different